2020
DOI: 10.1007/s40200-020-00640-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of emphysematous pyelonephritis and pyelonephritis in type 2 diabetes: a single-centre experience

Abstract: Purpose Emphysematous pyelonephritis (EPN) patients with type 2 diabetes (T2D) have severe complications and high morbidity with poor prognosis as compared to Pyelonephritis. The aim was to study clinical features, microbiological profile, complications of EPN and pyelonephritis in T2D patients. Methods This was a hospital-based prospective study done on 200 T2D patients with upper UTI. Various clinical, biochemical parameters and urine examination and culture were monitored. Patients were followed up for 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…A higher prevalence in the female gender has been described, as well as an average age presentation at 60 years. The main risk factors identified in case series in the literature are type 2 diabetes mellitus, up to 95% of patients with emphysematous pyelonephritis have poor glycemic control, followed by urinary tract obstruction [2,4,7].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A higher prevalence in the female gender has been described, as well as an average age presentation at 60 years. The main risk factors identified in case series in the literature are type 2 diabetes mellitus, up to 95% of patients with emphysematous pyelonephritis have poor glycemic control, followed by urinary tract obstruction [2,4,7].…”
Section: Discussionmentioning
confidence: 99%
“…Most type 2 diabetes patients exhibit inadequate glycemic control levels upon admission confirmed by HbA1C levels greater than 8% or presence of microvascular complications (diabetic retinopathy/ nephropathy) [7,8]. One study reported that neutrophiles´ ability to produce Neutrophil Extracellular Traps (NETs) was suppressed during hyperglycemia, leading to infection susceptibility; macrophage function is also altered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations